EKSPLORASI MODEL TINGKAT KECELAKAAN LALU - Haryadi, Bambang (Semarang State University, 2011)
Abstract: The objectives of the presents study wasÃÂ to explore mathematical models that could be usedÃÂ toÃÂ estimateÃÂ theÃÂ numberÃÂ ofÃÂ accidentsÃÂ onÃÂ interurbanÃÂ tollÃÂ roads.ÃÂ PreditiveÃÂ modelsÃÂ were developedÃÂ byÃÂ relatingÃÂ trafficÃÂ exposureÃÂ (averageÃÂ dailyÃÂ trafficÃÂ andÃÂ roadÃÂ sectionÃÂ length)ÃÂ withÃÂ the numberÃÂ ofÃÂ accidentsÃÂ perÃÂ unitÃÂ ofÃÂ time.Accident,ÃÂ roadwayÃÂ sectionÃÂ andÃÂ trafficÃÂ volumeÃÂ dataÃÂ were obtainedÃÂ fromÃÂ Jagorawi,ÃÂ JakartaCikampek,ÃÂ padaleunyi,ÃÂ andÃÂ palikanciÃÂ tollÃÂ road.ÃÂ AccidentÃÂ rate models were developed from those data usingÃÂ generalized linear modelling (GLM) techniques. The conclusionsÃÂ fromÃÂ theÃÂ study were:ÃÂ (1)ÃÂ linierÃÂ regression model wasÃÂ notÃÂ appropriateÃÂ toÃÂ beÃÂ usedÃÂ to predictÃÂ accidentsÃÂ number,ÃÂ becauseÃÂ accidentÃÂ occurenceÃÂ didÃÂ notÃÂ followÃÂ normalÃÂ distribution,ÃÂ (2) Poisson regression possessed accident occurence characteristics: descrete, rare and random, and (3)ÃÂ NegativeÃÂ BinomialÃÂ distributionÃÂ wasÃÂ moreÃÂ appropriateÃÂ toÃÂ representÃÂ accidentÃÂ occurence phenomenon with overdispersion. Keywords: accident rate, generalized linear modelling, Poisson regression, nagative binomial regression. ÃÂ Abstrak: PenelitianÃÂ iniÃÂ bertujuanÃÂ untuk mengeksplorasi model matematisÃÂ yangÃÂ dapatÃÂ digunakan untukÃÂ meramalkanÃÂ jumlahÃÂ kecelakaan,ÃÂ padaÃÂ suatuÃÂ ruasÃÂ jalanÃÂ tolÃÂ antarÃÂ kota.ÃÂ ModelÃÂ prediksi dikembangkanÃÂ denganÃÂ menghubungkanÃÂ paparanÃÂ lalulintas,ÃÂ yangÃÂ dinyatakanÃÂ denganÃÂ volume lalulintas dan panjang ruas jalan, dengan keselamatan, yang dinyatakan dalam jumlah kecelakaan per satuan waktu. DataÃÂ jalan, kecelakaan, danÃÂ lalulintas selama duaÃÂ tahun, diambil dariÃÂ jalanÃÂ tol antarÃÂ kotaÃÂ Jagorawi,ÃÂ Jakarta0Cikampek,ÃÂ PadaleunyiÃÂ danÃÂ Palikanci.ÃÂ ModelÃÂ tingkatÃÂ kecelakaan dikembangkan dari data tersebut dengan teknik generalized linear modelling (GLM), dan dikalibrasi denganÃÂ menggunakanÃÂ teknik0teknikÃÂ statistik.ÃÂ BeberapaÃÂ kesimpulanÃÂ yangÃÂ dapatÃÂ ditarikÃÂ dari penelitianÃÂ iniÃÂ adalah:ÃÂ (1)ÃÂ ModelÃÂ regresiÃÂ linierÃÂ denganÃÂ distribusiÃÂ normalÃÂ tidakÃÂ memadaiÃÂ untuk memprediksiÃÂ kecelakaan;ÃÂ tingkatÃÂ kecelakaanÃÂ tidakÃÂ terbuktiÃÂ mengikutiÃÂ distribusiÃÂ normal;ÃÂ (2) PenggunaanÃÂ regresi PoissonÃÂ lebih mencerminkan karakteristik kejadian kecelakaan: diskrit, acak, langka;ÃÂ ÃÂ ÃÂ danÃÂ (3)ÃÂ DistribusiÃÂ BinomialÃÂ NegatifÃÂ palingÃÂ baik merepresentasikanÃÂ kejadianÃÂ kecelakaan dengan adanya gejala overdispersi pada data. Kata kunci: tingkat kecelakaan, generalized linear modelling, regresi poisson, regresi binomial negatif.